DAMPAK STATUS KEBUGARAN JASMANI TERHADAP PENCAPAIAN HASIL BELAJAR SISWA DI SEKOLAH - Saputra, Benny; Hidayat, Taufiq; Wibowo, Sapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to find out how the impact of physical fitness status on the achievement of PJOK learning outcomes of students at SMP Negeri 2 Muncar. This study used quantitative design and a correlational approach, involving 32 students in grade IX. Students’ physical abilities are measured using the Indonesian Student Fitness Test (TKSI), and the fitness data is used as an indicator that has the potential to affect student participation and learning effectiveness, with learning outcomes represented through report card scores. The data analysis technique used Pearson Product Moment correlation and simple linear regression. The results of data processing were obtained from the physical fitness status category of 32 students as follows: (1) very good physical fitness status (0), (2) good physical status (0), (3) moderate physical status 14 students (44%), (4) poor physical status 18 students (56%), and (5) less than once (0), with an average of 57.94 and a standard deviation of 5.86. The percentage of PJOK learning outcomes from 32 students were: (1) excellent learning outcomes 6 students (19%), (2) good outcomes 14 students (44%), (3) moderate outcomes 12 students (37%), (4) poor learning outcomes (0), with an average of 78.34 and a standard deviation of 4.87. The R-value calculated as 0.62 with a significance value of p = 0.001 (p < 0.05), shows a positive and significant relationship. Physical fitness status contributed 38% to student learning outcomes, while the other 62% was influenced by other factors outside the study variables.